PENGARUH BERMAIN GAMES ONLINE TERHADAP HASIL BELAJAR SISWA KELAS XI DPIB SMKN 1 BUKITTINGGI - Asti, Mutiara; Arifin, Ari Syaiful Rahman (Jurnal Applied Science in Civil Engineering, 2024)
The research background is that the outcomes of learning from students in class XI DPIB SMKN 1 Bukittinggi in the Road and Bridge Construction (KJJ) subject are still many who are below the school's Minimum Completion Criteria (KKM) of 75. As for some of the causes of student incompleteness in the process of learning, many of the students in Class XI use smartphones to play online games. The research purpose is to reveal whether online games impact student outcomes of learning and how much impact. The research type used is research in descriptive method with approach by quantitative. The population for research were all class XI DPIB SMKN 1 Bukittinggi students consisting of two classes. The technique for sampling used Total Sampling with a sample size of 49 respondents. The techniques for data analysis used are test of normality, homogeneity, linearity, and hypothesis testing in the shape of t test (partial test) and the coefficient of determination.. Based research results, the sig. value for the online games (x) impact on learning outcomes (y) is 0.008 <0.05 and the t score is 2.781> t table 2.012 so the conclusion that accepted for Ha, which means that there is a online games (x) impact on learning outcomes (y). then it is also known that the r square score is 0.141, which means that the variable X impacted on variable Y is 14.1% with the rest being impacted by other variables not included in this research.